Analisis Teknikal Dan Analisis Fundamental Terhadap Kelayakan Pembelian Saham PT Bank Negara Indonesiaia Tbk (BBNI) - Titan Baihaqi Akbar Nugroho; Yanda Bara Kusuma (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The decision on the feasibility of purchasing a share is an indicator or criterion that is considered before finally deciding to invest or invest in the issuer. Researchers conducted technical analysis and fundamental analysis of PT Bank Negara Indonesia, Tbk. (BBNI) shares to find out whether the issuer's shares are suitable as issuers for investing or just for trading. Technical analysis and fundamental analysis are performed to see opportunity whether the shares are worthy of stock investment or not. Technical analysis is carried out using the simple moving average (SMA) and RSI methods. In addition, fundamental analysis is also carried out with several indicators such as price book value (PBV), price earning ratio (PER), debt equity ratio (DER), net probability margin (NPM), and earnings per share (EPS). In this study, the approach taken is a qualitative descriptive approach where data is presented in the form of narratives or detailed elaboration from experts. PT Bank Negara Indonesia (BBNI) shares are the oldest bank stocks that have a large market capitalization. This stock can also be said to have a relatively stable level of price fluctuation with a high level of profit and price. In terms of technical analysis and fundamental analysis, PT Bank Negara Indonesia (BBNI) shares are stocks that deserve to be an investment choice.